Resistance-heating of carbon nanotube yarns in different atmospheres. (July 2018) - Scholz, Maik; Hayashi, Yasuhiko; Khavrus, Vyacheslav; Chujo, Daiki; Inoue, Hirotaka; Hada, Masaki; Leonhardt, Albrecht; Büchner, Bernd; Hampel, Silke
Abstract: Annealing and functionalization of carbon nanotube yarns (CNYs) is a prospective way of increasing the electrical conductivity of this material. We show a novel way, the simultaneous annealing and instant coating of the CNY by its resistance-heating in atmospheres of hydrocarbons. This method is capable to preserve the lightweight properties of CNYs and increase the electrical conductivity. It could be raised by a factor of 2 through carbon deposition onto the yarns and the carbon nanotubes (CNTs) inside the yarn structure. By resistance-heating over a multistep process the conductivity could be even increased by a factor of 2.2. Comparison of annealing under atmosphere of different hydrocarbons and at different temperatures reveals the influence of resistance-heating on the structure of CNY. Graphical abstract: Image 1